PROJECT BASED DEBATING STRATEGY TO PROMOTE THE STUDENTS’SPEAKING ABILITY - Jaya, Aswadi; Hartono, Rudi; Wahyuni, Sri; Yulianto, Henrikus Joko (Proceedings of English Linguistics and Literature, 2024)
The purpose of this research is to examine how the online PjBL Mixidea debate technique ought to be incorporated into the digital technology learning orientations at UPGRI Palembang to help students with their public speaking. The study employed a quasi-experimental technique known as a non-equivalent UPGRI Palembang. Data collection procedures: (1) validity; (2) reliability. A statistically significant difference was found in post-experiment speaking test scores between the experimental group and the control group, as compared to pre-experiment scores. Results improved for students who were taught with the PjBL Mixidea online debate method. When compared to the control group, the experimental group generally performs better on post-tests. After administering eight different treatments to students in class X at UPGRI Palembang, the authors found that PjBL Mixidea's online debate strategy boosted students' public speaking skills. The students are in agreement that employing PjBL Mixidea's method of online discussion can help them become better public speakers. Students who were educated using PjBL Mixidea's online debate approach clearly outperformed those who were not.